(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article discusses the financial operations performed by Islamic banks, the processes of working with customers, and their differences from traditional banks. Today, financial transactions in Islamic banks: deposit, credit, letter of credit, settlement, payment transactions are analyzed and scientific conclusions are formed.